2019
DOI: 10.1021/acs.inorgchem.8b02531
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Chemical, Electrical, and Thermal Properties of n-Type NbFeSb

Abstract: We report on the structural, chemical, electrical, and thermal properties of n-type polycrystalline NbFeSb synthesized by induction melting of the elements. Although several studies on p-type conduction of this half-Heusler composition have recently been reported, including reports of relatively high thermoelectric properties, very little has been reported on the transport properties of n-type compositions. We combine transport property investigations together with short-and longrange structural data obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…4(b), gradually decreasing with temperature increasing. The main line shift is 0.089 mm s −1 at 295 K and 0.194 mm s −1 at 80 K. These results are very similar to the results recently reported [30] for an n-type NbFeSb sample. A fit to a standard second-order doppler relation [31], shown in Fig.…”
Section: B Mössbauer Measurementssupporting
confidence: 91%
See 1 more Smart Citation
“…4(b), gradually decreasing with temperature increasing. The main line shift is 0.089 mm s −1 at 295 K and 0.194 mm s −1 at 80 K. These results are very similar to the results recently reported [30] for an n-type NbFeSb sample. A fit to a standard second-order doppler relation [31], shown in Fig.…”
Section: B Mössbauer Measurementssupporting
confidence: 91%
“…Besides our work, Hobbis et al [30] also reported 57 Fe Mössbauer spectroscopy of NbFeSb, however in contrast with the p-type NbFeSb-1050 sample, their work focused on n-type NbFeSb. For n-type NbFeSb, two extra small doublets were observed with positions that differ from that of our measured satellite (0.65 mm s −1 ).…”
Section: Discussionmentioning
confidence: 56%
“…A similar refinement was performed for NbFeSb to quantify the Fe/4d Frenkel defects. 62 On the other hand, refining the Sn-free compounds (Zr 0.8 Ti 0.2 CoSb and ZrCoSb) ends up with physically meaningless results (negative occupation at the 4d sites) if the Co/4d defects are permitted. Therefore, the point-defect feature of the Sn-containing compounds is essentially different from the Sn-free ones.…”
Section: Calculation Of the Defect Formation Enthalpymentioning
confidence: 99%
“…This is consistent with the experimentally suggested intrinsic defects of Fe Nb or Fe i in NbFeSb. 20,21,37 Their donor behaviors imply the n-type character of the intrinsic NbFeSb compound. The formation of Fe i at the Fermi level close to the CBM is compensated by the formation of Fe Nb neutral defect, resulting in n-doped behavior.…”
Section: B Formation Energy Of Native Point Defectsmentioning
confidence: 99%
“…In 2019, Zhu et al successfully synthesized the corresponding n-type NbFeSb-based TE materials by substituting Co or Ir for Fe sites. Unfortunately, the maximum ZT value is quite low, ∼0.5 at 1000 K, [20][21][22] which is due to the poor electrical conductivity and low solid solubility of the dopants at the Fe sites. Until now, only the p-type NbFeSb compounds have been widely investigated, [23][24][25][26] and the corresponding n-type compounds are still scarce with much lower ZT value.…”
Section: Introductionmentioning
confidence: 99%